COMMUNITY SERVICE EDUCATION FOR EARLY DETECTION OF HIGH RISK OF PREGNANT WOMEN BASED ON HEALTHY TRADITIONS AT SALLY'S CLINIC - Deni Irawati; Herlina; Angel Kristiani Zai (Jurnal Masyarakat Indonesia (Jumas), 2024)
The Maternal Mortality Rate (MMR) is still the main indicator of the success of health development in Indonesia. One of the main challenges is the delay in early detection of pregnancy complications that are exacerbated by inaccuracies in traditional perceptions or myths in society. This community service activity aims to increase the knowledge, awareness, and independence of pregnant women in conducting early detection of high risk of pregnancy through the "Healthy Tradition" approach. This program is carried out at the Sally Clinic by involving pregnant women in the first, second, and third trimesters and families as moral supports. The method of activities is carried out through interactive counseling that integrates medical education with positive local cultural values. The results of the activity showed a significant increase in participants' understanding of pregnancy hazards and the importance of routine checkups. Through this approach, the stigma that medical science contradicts tradition can be minimized, so that pregnant women are more confident in maintaining the health of their fetus according to medical standards without abandoning their cultural identity.